Splenocyte Infusion and Whole-Body Irradiation for Induction of Peripheral Tolerance in Porcine Lung Transplantation: Modifications of the Preconditioning Regime for Improved Clinical Feasibility. Issue 7 (July 2017) - Jansson, Katharina; Dreckmann, Karla; Sommer, Wiebke; Avsar, Murat; Salman, Jawad; Siemeni, Thierry; Knöfel, Ann-Kathrin; Pauksch, Linda; Gottlieb, Jens; Frühauf, Jörg; Werner, Martin; Jonigk, Danny; et al.
Abstract : Background: Preoperative low-dose whole-body irradiation (IRR) with 1.5 and 7 Gy thymic IRR of the recipient, combined with a perioperative donor splenocyte infusion lead to reliable donor specific peripheral tolerance in our allogeneic porcine lung transplantation model. To reduce the toxicity of this preconditioning regime, modifications of the IRR protocol and their impact on allograft survival were assessed. Methods: Left-sided single lung transplantation from major histocompatibility complex and sex mismatched donors was performed in 14 adult female minipigs. Recipient animals were exposed to 3 different protocols of nonmyeloablative IRR within 12 hours before transplantation. All animals were administered a donor splenocyte infusion on the day of lung transplantation. Intravenous pharmacologic immunosuppression was withdrawn after 28 postoperative days. Allograft survival was monitored by chest radiographs and bronchoscopy. Results: IRR prolonged transplant survival in a dose- and field-dependent manner. Shielding of the bone marrow from IRR (total lymphoid IRR at 1.5 and 7 Gy thymic IRR) significantly reduced protocol toxicity defined as thrombocytopenia and consecutive increased bleeding propensity, but had a less effective impact on graft survival. Whole-body IRR at 0.5 and 7 Gy thymic IRR proved to be ineffective for reliable tolerance induction. Eventually, high levels of circulating CD4 + CD25 high regulatory T cells were present in long-term survivors. Conclusions: These data show that the infusion of donor-specific alloantigen in combination with IRR is efficient once a threshold dose is exceeded.